2015
DOI: 10.1371/journal.pone.0141509
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Attenuates Inflammatory Responses in BV-2 Microglial Cells: Role of MAPKs on the Nrf2 Pathway and Induction of Heme Oxygenase-1

Abstract: A large group of flavonoids found in fruits and vegetables have been suggested to elicit health benefits due mainly to their anti-oxidative and anti-inflammatory properties. Recent studies with immune cells have demonstrated inhibition of these inflammatory responses through down-regulation of the pro-inflammatory pathway involving NF-κB and up-regulation of the anti-oxidative pathway involving Nrf2. In the present study, the murine BV-2 microglial cells were used to compare anti-inflammatory activity of querc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 56 publications
3
106
1
1
Order By: Relevance
“…Flavonoids may positively influence health through their well-documented effects on cellular antioxidant status and inflammation (68). Flavonoids may augment endogenous antioxidant defenses through nuclear factor, erythroid 2-like 2 (Nrf2) activation of antioxidant response elements of genes encoding antioxidant enzymes in vitro (69,70). Anthocyanin intake has been shown to reduce systemic inflammation markers in humans while also suppressing LPS activation of NF-kB in human monocytes (71).…”
Section: Flavonoids As Atheroprotective Components Of the Dietmentioning
confidence: 99%
“…Flavonoids may positively influence health through their well-documented effects on cellular antioxidant status and inflammation (68). Flavonoids may augment endogenous antioxidant defenses through nuclear factor, erythroid 2-like 2 (Nrf2) activation of antioxidant response elements of genes encoding antioxidant enzymes in vitro (69,70). Anthocyanin intake has been shown to reduce systemic inflammation markers in humans while also suppressing LPS activation of NF-kB in human monocytes (71).…”
Section: Flavonoids As Atheroprotective Components Of the Dietmentioning
confidence: 99%
“…2a-c). The indicated concentrations of quercetin, honokiol, and C3G had been discussed to pose no toxicity to BV-2 cells in previous studies Sun et al 2015;Kaushik et al 2012). Fig.…”
Section: Quercetin and Honokiol But Not Cyanindin-3-oglucoside Signmentioning
confidence: 97%
“…Previous studies from our laboratory as well as from others have demonstrated the effects of botanicals, such as quercetin from berries and honokiol from the magnolia bark, to mitigate microglial-induced production of NO and reactive oxygen species (ROS) upon stimulation by LPS or pro-inflammatory cytokines (Chuang et al 2013;Jiang et al 2014). These studies also unveil differences in potency in their ability to mitigate antioxidative and anti-inflammatory responses Sun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin and epigallocatechin gallate (EGCG) reduce the production of proinflammatory cytokines by macrophages and microglia 142, 143, 144, 145. Moreover, flavonoids, such as quercetin, suppress the capacity of monocytes to cross the BBB and limit the uptake of myelin by macrophages 146, 147.…”
Section: Flavonoidsmentioning
confidence: 99%